Pengaruh Penerapan Sistem Akuntansi Keuangan Pemerintah Daerah, Pemanfaatan Teknologi Informasi Dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Daerah (Studi Kasus Pada Organisasi Perangkat Daerah (OPD) Provinsi DKI Jakarta Tahun 2022) - Sri Rahayu; Alfanisha Dewi Kanita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Regional financial reports are an important factor that must be carried out by the government in the implementation of regional autonomy to provide decision-making information. This study is to find out how the application and the effect of the use of local government financial accounting systems, the use of information technology and control systems on the quality of the financial statements of OPD DKI Jakarta Province. This research is a quantitative research. The sample used in this study was 84 respondents consisting of heads of fields and staff in accounting and finance at 42 OPD. The data analysis model of this research is multiple linear regression using IBM SPSS version 26 software. The results show that the application of local government financial accounting systems, the use of information technology and internal control systems in the DKI Jakarta Provincial OPD has a positive effect. Simultaneously significant to the quality of regional financial reports. The application of the local government financial accounting system and the partial use of information technology have no effect on the quality of regional financial reports. However, the internal control system shows a partial positive effect on the quality of regional financial reports.